Regulation of human placental drug transporters in HCV infection and their influence on direct acting antiviral medications. (September 2018) - Pfeifer, Emily; Parrott, Jessica; Lee, Gene T.; Domalakes, Ericka; Zhou, Helen; He, Lily; Mason, Clifford W.
Abstract: Introduction: The objectives of this study were to determine how HCV infection affects placental drug transporters, and to determine the role of drug transporters on the cellular accumulation of direct-acting antiviral drugs in human trophoblasts. Methods: Eighty-four ABC and SLC transporter genes were first screened in normal and HCV infected pregnant women using PCR profiler array. The changes in expression were confirmed by qPCR and Western blot. The impact of selected drug transporters on the cellular accumulation of radiolabeled antiviral drugs sofosbuvir, entecavir, and tenofovir was measured in primary human trophoblasts (PHT) and BeWo b30 cells in the presence or absence of transporter-specific inhibitors. PHT were then treated with CL097, ssRNA40, and imquimod to determine the impact of Toll-like receptor (TLR) 7/8 activation on drug transporter expression. Results: The expression of the ABC efflux transporters ABCB1/P-gp and ABCG2/BCRP was increased in placenta of women with HCV, while the nucleoside transporters SLC29A1/ENT1 and SLC29A2/ENT2 remained unchanged. The accumulation of sofosbuvir and tenofovir was unaffected by inhibition of these transporters in trophoblast cells. Entecavir accumulation was decreased by the inhibition of ENT2. P-gp and BCRP inhibition enhanced entecavir accumulation in BeWo b30, but not PHT. Overall, there was little effect of TLR7/8 activation on these drug transporters, and the accumulation of entecavir in PHT. Discussion: The data suggest that expression of placental drug transporters and selection of antiviral drug may impact fetal drug exposure in pregnancies complicated by HCV infections. Highlights: P-gp and BCRP mRNA and protein expression were increased in placenta of women with HCV. Sofosbuvir accumulation in trophoblast cells was not affected by transporter inhibition. ENT2 was involved in entecavir accumulation into trophoblast cells. ENT1/2, P-gp, and BCRP were not involved in tenofovir accumulation in trophoblast cells. Activation of TLR7 and TLR8 had little effect on transporter expression.